Estimation of parameters from progressively censored data using EM algorithm - Ng, H.K.T.; Chan, P.S.; Balakrishnan, N. (Computational statistics & data analysis, 2002)
EM algorithm is used to determine the maximum likelihood estimates when the data are progressively Type II censored. The method is shown to be feasible and easy to implement. The asymptotic variances and covariances of the ML estimates are computed by means of the missing information principle. The methodology is illustrated with two popular models in lifetime analysis, the lognormal and Weibull lifetime distributions.